Formation, Spectral and Theoretical Studies of 1-(4,4-Dimethyl-2,6-Dithioxo-1,3,5-Triazinan-1-yl)-3-(Diethylaminocarbonyl)Thiourea - Mohamad J. Al-Jeboori (Journal of Global Pharma Technology, 2018)
The reaction of diethylcarbamic chloride (one mole equivalent), ammonium thiocyanate (two mole equivalents) and thiosemicarbazide (one mole equivalent) in an acetone medium resulted in the formation of the unexpected4,4-dimethyl-2,6-dithioxo-1,3,5-triazinan-1-yl)-3-(diethylaminocarbonyl)- thiourea3in 83% yield. The chemical structure of the title compound was confirmed by IR, NMR and elemental analysis. Further, a suggested mechanism has been proposed to illustrate the route for the formation of the title compound. In addition, theoretical evaluations of the stable geometries of compound3were carried out using semi-empirical molecular quantum calculations with the PM3 method.Keywords: Thiosemicarbazone, Cyclization reaction, Spectroscopic analysis, Computational calculations.